2021
DOI: 10.1016/j.ssmqr.2021.100026
|View full text |Cite
|
Sign up to set email alerts
|

The lived experience of healthcare professionals working frontline during the 2003 SARS epidemic, 2009 H1N1 pandemic, 2012 MERS outbreak, and 2014 EVD epidemic: A qualitative systematic review

Abstract: Objective To synthesize qualitative literature exploring the lived experience of healthcare workers (HCWs) who cared for patients during the following infectious disease outbreaks (IDOs): the 2003 SARS epidemic, 2009 H1N1 pandemic, 2012 MERS outbreak, and 2014 EVD epidemic. We aim to reveal the collective experience of HCWs during these four IDOs and to create a reference for comparison of current and future IDOs. Methods Three electronic databases were searched, yieldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…According to O'Leary et al [ 44 ], Ahmed et al [ 45 ], and Kamruzzaman [ 46 ], this is not surprising, as the initial fear caused by the unprecedented nature of the COVID-19 virus caused many to behave selfishly and disregard humanity. This fear was compounded by the emergence of new social regulations [ 11 ], as well as misinformation and rumors from numerous dubious sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to O'Leary et al [ 44 ], Ahmed et al [ 45 ], and Kamruzzaman [ 46 ], this is not surprising, as the initial fear caused by the unprecedented nature of the COVID-19 virus caused many to behave selfishly and disregard humanity. This fear was compounded by the emergence of new social regulations [ 11 ], as well as misinformation and rumors from numerous dubious sources.…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh, a low-middle-income country with one of the world's most densely populated areas [ 10 ], people were discouraged from participating in community gatherings and various cultural rituals, including funerals. They were encouraged to stay home, engage in social distancing, adhere to home quarantine guidelines, and adopt other protective measures due to the fear of COVID-19 [ 11 ]. However, how rituals for the deceased were conducted during the COVID-19 pandemic was also influenced by societal norms.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the experiences of staff who cared for COVID-19 patients, HCWs who are involved in the frontline care of SARS, MERS, and EVD patients were afraid of contracting the virus or spreading it to their loved ones and were aware that they were risking their safety because of this involvement [ 56 ]. The responses of our sample emphasize the emotional experience with regard to the vaccination status of the patients and the representation of the vaccine as a safety tool for their health.…”
Section: Discussionmentioning
confidence: 99%
“…Health care workers (HCWs) are essential for responding to the effects of pandemics. Previous studies on the experiences of HCWs during the aforementioned outbreaks have shown that HCWs are at grave risk for contracting new and dangerous diseases, and they work under physical and psychological stress as they navigate new clinical and non-clinical challenges in the health care system (10)(11)(12)(13)(14). These challenges include but are not limited to, increased workloads and sta ng shortages, inadequate personal protective equipment (PPE), limited opportunities to engage with policymakers, lack of timely training on new procedures and protocols, inconsistent communication from multiple sources, lack of targeted and context-speci c communication and frequent modi cation of infection control procedures and public health recommendations, which increase feelings of uncertainty among HCWs (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the experiences of HCWs during the aforementioned outbreaks have shown that HCWs are at grave risk for contracting new and dangerous diseases, and they work under physical and psychological stress as they navigate new clinical and non-clinical challenges in the health care system (10)(11)(12)(13)(14). These challenges include but are not limited to, increased workloads and sta ng shortages, inadequate personal protective equipment (PPE), limited opportunities to engage with policymakers, lack of timely training on new procedures and protocols, inconsistent communication from multiple sources, lack of targeted and context-speci c communication and frequent modi cation of infection control procedures and public health recommendations, which increase feelings of uncertainty among HCWs (10)(11)(12)(13)(14)(15). Many of the recommendations emanating from previous outbreaks have called for improved collaboration and communication between public health and primary care, increased workforce sta ng and support, provision of training for redeployed staff and upscaling the knowledge and skills of HCWs in emergency management, infection prevention and control and pandemic preparedness plans (12,15,16).…”
Section: Introductionmentioning
confidence: 99%